Cowpeas vs. soybeans: Can valorization bridge the nutritional gap for sustainable animal feeding systems in the Global South? - Mashiloane, Thabang; Mlambo, Victor; Mhlongo, Godfrey; Dibakoane, Siphosethu R.; Mnisi, Caven M. (Frontiers in Sustainable Food Systems, 2025)
Heavy dependence on soybeans for non-ruminant diets is unsustainable in regions where poor growing conditions limit production. Across much of the Global South, local supply rarely meets demand, forcing costly imports that erode feed profitability. Indigenous pulses such as cowpeas, well-adapted to local climates and soils, offer a practical alternative or complement to soybean protein. Cowpeas are rich in protein and contain unique bioactive compounds with antimicrobial, antioxidant, anti-inflammatory, anticancer, and immunostimulatory potential. However, their nutritional quality remains inferior to soybeans due to anti-nutritional factors (ANFs) and an imbalanced amino acid profile, particularly a deficiency in sulfur-containing amino acids like methionine and cysteine. Additionally, like many legumes, cowpeas also exhibit relatively low protein digestibility, which further limits their direct use in non-ruminant diets. To unlock the potential of cowpeas as a sustainable feed ingredient, effective valorization strategies are essential. Techniques such as solid-state fermentation, sprouting, soaking, roasting, boiling, dehulling, extrusion, hot-air drying, and enzymatic treatments have been explored to enhance nutritional value. These methods aim to reduce ANFs, improve amino acid balance, and increase protein digestibility. This systematic review synthesizes current research on the mechanisms and efficacy of cowpea valorization techniques, with a particular focus on their capacity to achieve nutritional and functional parity with soybean meal in non-ruminant diets. By critically evaluating the impact of these approaches, the review provides a foundation for optimizing cowpea utilization in animal feeding systems. Such advancements could contribute significantly to climate-resilient, economically viable, and nutrition-secure food systems in the Global South.